Incidental Memory Encoding Assessed with Signal Detection Theory and Functional Magnetic Resonance Imaging (fMRI) - Clemens, Benjamin; Regenbogen, Christina; Koch, Kathrin; Backes, Volker; Romanczuk-Seiferth, Nina; Pauly, Katharina; Shah, N. Jon; Schneider, Frank; Habel, Ute; Kellermann, Thilo (Frontiers in Behavioral Neuroscience, 2015)
In functional magnetic resonance imaging (fMRI) studies that apply a ‘subsequent memory’ approach, successful encoding is indicated by increased fMRI activity during the encoding phase for hits versus misses, in areas underlying memory encoding such as the hippocampal formation. Signal-detection theory (SDT) can be used to analyze memory-related fMRI activity as a function of the participant’s memory trace strength (d’). The goal of the present study was to use SDT to examine the relationship between fMRI activity during incidental encoding and participants’ recognition performance. To implement a new approach, post-experimental group assignment into High- or Low Performers (HP or LP) was based on 29 healthy participants' recognition performance, assessed with SDT. The analyses focused on the interaction between the factors group (HP vs. LP) and recognition performance (hits vs. misses). A whole-brain analysis revealed increased activation for HP versus LP during incidental encoding for remembered versus forgotten items (hits > misses) in the insula / temporo-parietal junction (TPJ) and the FFG. Parameter estimates in these regions exhibited a significant positive correlation with (d’). As these brain regions are highly relevant for salience detection (insula), stimulus-driven attention (TPJ), and content-specific processing of mnemonic stimuli (FFG), we suggest that HPs’ elevated memory performance was associated with enhanced attentional and content-specific sensory processing during the encoding phase. We provide first correlative evidence that encoding-related activity in content-specific sensory areas and content-independent attention and salience detection areas influences memory performance in a task with incidental encoding of facial stimuli. Based on our findings, we discuss whether the aforementioned group differences in brain activity during incidental encoding might constitute the basis of general differences in memory performance between HP and LP.